2021
DOI: 10.1158/1078-0432.ccr-21-1133
|View full text |Cite
|
Sign up to set email alerts
|

A Neoadjuvant Chemotherapy Trial for Early Breast Cancer is Impacted by COVID-19: Addressing Vaccination and Cancer Trials Through Education, Equity, and Outcomes

Abstract: The COVID-19 pandemic has affected cancer clinical trials, but there is limited information about its impact. During the pandemic, from February 2020 to January 2021, 4.5% of patients treated on the neoadjuvant I-SPY 2 trial for high-risk early breast cancer experienced interruption of treatment due to COVID-19 infection, providing information on the pandemic's impact on clinical trials. While COVID-19 vaccination is expected to reduce attrition from trials, vaccine hesitancy and poor vaccine access in underse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…36 Similarly, cancer-specific education and communication about the risks associated with COVID versus risk of side effects from COVID vaccines from trusted sources may have alleviated uncertainties or concerns around vaccination. Our findings support recent international research, which also found that breast cancer patients sought information about vaccines from their oncologists 37 and that HPs can assist in the decision making related to COVID-19 vaccines. 20 To support this, once vaccines have been proven to be safe and effective in the general population, clinical trials should focus on vulnerable population groups, such as those with compromised immune systems.…”
Section: Accessibilitysupporting
confidence: 89%
See 2 more Smart Citations
“…36 Similarly, cancer-specific education and communication about the risks associated with COVID versus risk of side effects from COVID vaccines from trusted sources may have alleviated uncertainties or concerns around vaccination. Our findings support recent international research, which also found that breast cancer patients sought information about vaccines from their oncologists 37 and that HPs can assist in the decision making related to COVID-19 vaccines. 20 To support this, once vaccines have been proven to be safe and effective in the general population, clinical trials should focus on vulnerable population groups, such as those with compromised immune systems.…”
Section: Accessibilitysupporting
confidence: 89%
“…Further, research 35 , 39 indicates that education interventions, such as webinars delivered by experts (oncology and disease specialists), can impact patient perspectives regarding COVID‐19 vaccine safety and effectiveness, as well as shift intentions toward vaccination. Potter and colleagues 37 suggest that government agencies and healthcare organizations can also play an important role in media and education campaigns to provide evidence‐based information and prevent the spread of misinformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative chemotherapy, radiotherapy, molecular targeted therapy and endocrine therapy for breast cancer patients all need to follow strict treatment norms. During the COVID-19 pandemic, delayed treatment for various reasons may lead to unsatisfactory efficacy, thus affecting patient's disease-free survival and overall survival (8,9). For early-stage breast cancer, patients with delayed chemotherapy over 8 weeks after surgery had a higher risk of all-cause mortality than those with standardized chemotherapy (10).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 was rst found in Central China (Wuhan, the capital of Hubei province) at the end of December 2019 [26]. Many reports have explored the relationship of COVID-19 with cancer [27][28][29]. Hoang, T. et al reported that genetic susceptibility of ACE2 and TMPRSS2 in GC was associated with the susceptibility to COVID-19 infection [30].…”
Section: Discussionmentioning
confidence: 99%